The Effectiveness of Using Le Duo Tir Tools in Increasing Petanque Shooting Accuracy - Lubis, Muhammad Ridwan; Permadi, Andi Gilang; Muhaimin, Ali (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
The problem in this study is that the limitations of special equipment in shooting training cause low accuracy in shooting for NTB petanque athletes. The aim of this study was to determine the effectiveness of using the Le Duo Tir tool in increasing the accuracy of shooting petanque. A quasi-experimental research method was used in this study, which consisted of an experimental group and a control group with a test and post-test research design with non-equivalent control-group design. Data analysis begins with the prerequisite test Kormogorov-Smirnov Test before conducting the Paired Sample T-Test, homogeneity test for the post-test data of the experimental group and control group, and continued with the Independent Sample T-Test. The results of the Independent Sample T-Test test obtained the value of Sig. (2-tailed) of 0.000 <0.05, it is concluded that there is a difference in the effect of shooting accuracy between the experimental group and the control group, but the use of the Le Duo Tir tool is stated to be more effective in increasing shooting accuracy (mean = 28.90) than conventional training ( mean=20.40).